Does gold investment offer protection against stock market losses? evidence from five countries - Mohd Fahmi Ghazali; Hooi, Hooi Lean; Zakaria Bahari (World Scientific Publishing Co Pte Ltd, 2020)
This study aims to analyze the characteristics of gold as a diversifier, a hedge or a safe haven against the stock market collapse in five countries. We propose the standard TGARCH and quantile technique in the TGARCH frameworks. Gold exhibits considerable evidence of the strong hedge in India and the US, and diversified role in China. With regards to its role as a safe haven, gold retains its status as a key investment particularly in a country where gold has a preeminent cultural role, i.e., India, as well as in the US and the UK. On the other hand, gold only plays a minor role in emerging markets like in Malaysia. Therefore, investors in India and the US can use gold to protect against losses in the stock market at all times, while in the UK, gold is only viewed as a profitable asset to own during the stock market collapse. Contrariwise, Chinese investors should hold a well-diversified portfolio to earn sustainable returns and offer protection against the stock market collapse. We conclude that the recent worldwide financial crises have increased the investment demand for gold in over the last seventeen years at least.